Franklin rides a bike - Bourgeois, Paulette; Clark, Brenda (Toronto : Kids Can Press, 1998)
Determined to ride his bike without training wheels, Franklin cannot understand why it seems so easy for his friends - and why it is so hard for him."
"Weekly Reader Books"--P. [4] of cover.
Previously published: Toronto: Kids Can Press, 1997.
2.
3-7.
Keywords: Franklin (Fictitious character : Bourgeois) -- Juvenile fiction; Training wheels -- Juvenile fiction; Cycling -- Juvenile fiction; Persistence -- Juvenile fiction; Frustration -- Juvenile fiction; Perseverance (Ethics) -- Juvenile fiction; Picture books for children